The need to Include Psychiatry subject separately in the MBBS Curriculum - Subedi, S (Journal of Psychiatrists' Association of Nepal, 2015)
N/AJ Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 1-2DOI: http://dx.doi.org/10.3126/jpan.v3i2.12377